Younger genes are less likely to be essential than older genes, and duplicates are less likely to be essential than singletons of the same age - Chen, Wei-Hua; Trachana, Kalliopi; Bork, Peer (Molecular biology and evolution, 2012)
Recently duplicated genes are believed to often overlap in function and expression. A priori, they are thus less likely to be essential. Although this was indeed observed in yeast, mouse singletons and duplicates were reported to be equally often essential. This contradiction can only partly be explained by experimental biases. We herein show that older genes (i.e., genes with earlier phyletic origin) are more likely to be essential, regardless of their duplication status. At a given phyletic gene age, duplicates are always less likely to be essential compared with singletons. The “paradoxical” high essentiality among mouse gene duplicates is then caused by different age profiles of singletons and duplicates, with the latter tending to be derived from older genes.